Analysis of the Effect of Polyethylene Residues Recycling on Mechanical Performance and Collapse Behaviour in Concrete (Journal of Technology Research, 2025)
This study aims to analyse the effect of adding crushing recycled High-Density Polyethylene (HDPE) residues to concrete mixtures as a partial substitute component for aggregates, with different volumetric ratios (0%, 10%, 20%, and 30%), as well as the introduction of HDPE fibres in a fixed volumetric ratio (1%) to help in flexural resistance, to evaluate the effect of these additives on the mechanical properties of concrete. Concrete samples were prepared according to these ratios and subjected to destructive and non-destructive tests, such as compressive strength, flexural, and impact load, in addition to examining collapse patterns after the test. Preliminary results showed that when 30% of HDPE was added may contribute to improved impact resistance, while leading to a decrease in compressive and bending resistance compared with the reference mixture, which can be compensated by using appropriate metal or chemical additives. Fibers have also helped to improve breakdown behaviour and reduce cracks. Visual analysis of collapses and the pattern of cracks also showed that the introduction of HDPE into concrete moves it from the traditional brittle state to the soft state, the higher its proportion in the mixture. In order to improve the sustainability of the materials used in construction and lessen environmental pollution brought on by plastic waste, the study suggests using the proportions of these materials that have been investigated in non-structural or light structural applications.
Keywords: Plastic concrete; HDPE; Mechanical performance; Failure behaviour